PENERAPAN STRATEGI GUIDED NOTE TAKING DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD INPRES RAPPOCINI MAKASSAR - Indriani; Andi Dody May Putra Agustang; Hudayah Sulaiman; Ramdani Sidik; A Hardiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of the Guided Note Taking learning strategy in improving student learning outcomes in Social Studies (IPS) at the elementary school level. The study employed a qualitative approach using a classroom action research (CAR) design, conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 19 fifth-grade students at SD Inpres Rappocini in Makassar. Data collection techniques included observation, testing, and documentation, while data analysis was conducted using both qualitative and quantitative descriptive methods. The results of the study indicate that the implementation of the Guided Note Taking strategy was able to significantly improve student learning activities and learning outcomes. Teachers’ instructional activities improved from the “adequate” category to “good,” followed by an increase in students’ learning activities, who became more active in note-taking, discussion, and understanding the material. Additionally, students’ learning outcomes improved from the “very low” category in Cycle I to the “very high” category in Cycle II, with the majority of students achieving the Minimum Competency Criteria (KKM). These findings indicate that the Guided Note Taking strategy is effective in improving the quality of the social studies learning process and outcomes. This study contributes to the development of learning strategies oriented toward active student engagement and provides practical implications for teachers in designing more interactive and effective learning experiences. Keywords: Guided Note Taking, learning outcomes, social studies learning, elementary school, classroom action research